(untitled) (Italian Journal of Public Health, 2005)
Serotype Enteritidis is still the main serotype infecting humans and poultry worldwide. Subtyping of isolates belonging to this serotype is difficult, because of the wide clonal circulation of a few bacterial clones. This study presents the results of the characterization of 49 isolates of S. Enteritidis identified at the southern Italy Centre for Enteric Pathogens (CEPIM) during the years 2002-2003 by the methods of Pulsed Field Gel Electrophoresis (PFGE) and Single-Enzyme Amplified Fragment Length Polymorphism (SE-AFLP). Clustering of the strains by SE-AFLP and PFGE is very similar, but the first technique is more rapid and user-friendly and does not require sophisticated equipment. Further work is needed for a more accurate assessment of SEAFLP, but preliminary results suggest it could be a promising support to epidemiological investigations.